Pentingnya Hijauan Pakan untuk Mendukung Usaha Ternak Potong di Desa E2 (Sumber Mulya) - Muhammad Rido; Nurliani Erni (Cv. Utility Project Solution, 2023)
One of the communities in Central Kalimantan's Bulik District, Lamandau Regency, is Sumber Mulya Village. In general, the oil palm plantation industry, along with a number of fishing and cattle enterprises, make up the community's economy. There is currently no broiler poultry company in the neighborhood; instead, the livestock industry consists of ruminant animals like cows and goats. Implementing community service has as its goal raising public awareness of the value of fodder in the beef cattle industry. Utilizing methods of counseling and discussion, the implementation was carried out. The procedure of locating the service area is the first step in carrying out the activity. This is followed by community service and visits and interviews with the village chief. Breeders in E2 Village (Sumber Mulya) became more interested in the kinds of forages that could produce high yields as a result of the outreach activities on the importance of forage to support the beef cattle business. Breeders were also very eager to discuss the challenges they faced when raising their livestock. It is believed that by engaging in this activity, breeders will become more aware of the importance of feed to their livestock's ability to produce at their peak.